A new case of Rafiq syndrome with coexisting thyroid dyshormonogenesis type 6 in a Chinese patient: case report and literature review - Qi, Ruifang; Guo, Hanfei; Li, Rongmin; Chang, Jie; Wu, Di; Sang, Yanmei (Frontiers in Endocrinology, 2025)
Rafiq syndrome is a rare autosomal recessive genetic disorder first described by Rafiq et al. in 2011.With an extremely low incidence rate, just over 40 cases have been reported worldwide. This condition is caused by mutations in the MAN1B1 gene, which encodes a member of the glycosyl hydrolase family 47.The primary clinical features of Rafiq syndrome include intellectual and motor developmental delay, distinctive facial features, truncal obesity, and hypotonia. We described a case of Rafiq syndrome with coexisting thyroid dyshormonogenesis type 6 in a Chinese Patient. The patient presented with distinctive facial features (small forehead, wide eye distance, small bilateral eye fissures, low nose bridge, protruding nose, short philtrum, small chin, large ears, short neck), borderline intellectual delay, truncal obesity, abnormal coagulation function, abnormal electroencephalogram, which were similar with the clinical manifestations of Rafiq syndrome reported in the literature. In addition to the above-mentioned abnormalities, the child also has thyroid dyshormonogenesis type 6. Genetic testing has identified compound heterozygous mutations in the MAN1B1 gene: c.1281_1303delCATCCACGCCTGTGTCTGGAAGA and c.2011C>T, and one heterozygous mutation in the DUOX2 gene: c.650A>G, which is new variant of uncertain clinical significance. The clinical manifestations and genetic testing of patients can help diagnose Rafiq syndrome. To the best of our knowledge, this combination of genetic defects is unique and has not been previously reported in the literature.